2018
DOI: 10.1007/s00167-018-5015-2
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid high tibial osteotomy is superior to medial opening high tibial osteotomy for the treatment of varus knee with patellofemoral osteoarthritis

Abstract: Retrospective comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…‖ We found that 3 studies compared the use of opening wedge and closing wedge approaches, 17,18,41 whereas 2 studies evaluated opening and closing wedge approaches using a case series design. 3,26 A total of 117 patients underwent a hybrid PTO approach (variously described as 33% medial opening combined with a 67% lateral closed wedge and locking plate fixation 31 ; double osteotomies involving a lateral distal femoral closure and a proximal tibial medial opening 38 ; and modified Weber technique with a step-cut osteotomy to the proximal fibula and fixation with a bent one-half tubular plate and 2 screws). 39 A total of 79 patients underwent PTO with the opening wedge hemicallotasis technique (1 study 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…‖ We found that 3 studies compared the use of opening wedge and closing wedge approaches, 17,18,41 whereas 2 studies evaluated opening and closing wedge approaches using a case series design. 3,26 A total of 117 patients underwent a hybrid PTO approach (variously described as 33% medial opening combined with a 67% lateral closed wedge and locking plate fixation 31 ; double osteotomies involving a lateral distal femoral closure and a proximal tibial medial opening 38 ; and modified Weber technique with a step-cut osteotomy to the proximal fibula and fixation with a bent one-half tubular plate and 2 screws). 39 A total of 79 patients underwent PTO with the opening wedge hemicallotasis technique (1 study 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is not clear whether the postoperative changes observed in this study induce osteoarthritic progression of the patellofemoral joint, 10 , 11 it can be stated that correction of severe varus deformity by either DLO or isolated MOWHTO induces similar changes in the biomechanical environment of the patellofemoral joint. Since it has been reported that knees with severe varus deformity is generally combined with severe patellofemoral arthritis, 32 osteotomy procedures that exert less influence on the patellar position such as distal-tuberosity osteotomy, 33 , 34 closed wedge HTO, 8 , 28 and hybrid HTO 35 , 36 , 37 should be considered as alternative surgical options on the tibial side.…”
Section: Discussionmentioning
confidence: 99%
“…The intraobserver and interobserver reliability for the ICRS cartilage grading using arthroscopy was 0.881 (95% confidence interval (CI) 0.776-0.937) and 0.842 (95% CI 0.720-0.913), respectively, and 0.981 (95% CI 0.858-0.983) and 0.903 (95% CI 0.504-0.983), respectively, for ROM. Therefore, all radiographic parameters were measured with high reliability and reproducibly [15].…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopy was routinely performed prior to surgery to evaluate the degree of cartilage degeneration, quantified using the International Cartilage Repair Society (ICRS) grading system [14]. The surgical procedure used for OWHTO has previously been described [15]. Briefly, the medial proximal tibia was exposed using a J-shaped incision, and the superficial medial collateral ligament and the pes anserinus were released.…”
Section: Surgical Procedures and Assessmentmentioning
confidence: 99%